1982
DOI: 10.1002/1097-0142(19821115)50:10<2122::aid-cncr2820501025>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell myeloma in a patient with a cutaneous T-cell lymphoma

Abstract: A case is reported, believed to be the first, of a patient with a long‐standing cutaneous T‐cell lymphoma, in whom disseminated plasma cell myeloma subsequently developed shortly before the patient died. It is postulated that, rather than to a chance association, the second B‐cell neoplasm evolved under the sustained inducer‐cell activity of the malignant lymphocytes of the cutaneous T‐cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…The contributory effect of monoclonal proliferation of Tlymphocytes in the development of a B-cell lymphoma via cytokines or reactivation of a dormant virus has been postulated (7,18,19). In addition, malignant transformation of pluripotent stem cells, which generate both T-cells and Bcells (18), may provide a possible explanation in some cases for a composite T-cell and B-cell lymphoma (19,20 …”
Section: O P S Y S P E C I Me N F R O M T H E N E C K S H O W-mentioning
confidence: 98%
“…The contributory effect of monoclonal proliferation of Tlymphocytes in the development of a B-cell lymphoma via cytokines or reactivation of a dormant virus has been postulated (7,18,19). In addition, malignant transformation of pluripotent stem cells, which generate both T-cells and Bcells (18), may provide a possible explanation in some cases for a composite T-cell and B-cell lymphoma (19,20 …”
Section: O P S Y S P E C I Me N F R O M T H E N E C K S H O W-mentioning
confidence: 98%
“…In addition, according to various, sporadic reports, multiple myeloma is occasionally associated with other peripheral T-cell lymphoma subtypes, including cutaneous anaplastic large T-cell lymphoma, Sezary syndrome, mycosis fungoides, and primary T-cell lymphoma of the bone (Bryant et al 1982;Weiss et al 1984;Brumana et al 1993;Cartron et al 1999;Wickenhauser et al 1999;Takami and Mizunoya 2000;Gernone et al 2002;Hwang et al 2008;Tangour et al 2011). In general, the secondary myeloma occurs several years after the initial diagnosis and the subsequent treatment of the T-cell lymphoma (Bryant et al 1982;Weiss et al 1984;Brumana et al 1993;Wickenhauser et al 1999;Gernone et al 2002;Zettl et al 2002;Hwang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the secondary myeloma occurs several years after the initial diagnosis and the subsequent treatment of the T-cell lymphoma (Bryant et al 1982;Weiss et al 1984;Brumana et al 1993;Wickenhauser et al 1999;Gernone et al 2002;Zettl et al 2002;Hwang et al 2008). Various authors have suggested that the secondary neoplasms are potentially related to immunoregulatory disturbances caused by the primary lymphomas and that the malignant plasma cells may evolve from a sustained inducing stimulus provided by the neoplastic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, however, no lineage infidelity or promiscuous rearrangements could be demonstrated by Southern blot analysis. A helper activity of neoplastic T lymphocytes, which could be specific for a B-cell clone, has been proposed as the triggering mechanism for B lymphoma development by workers who claim that T-cell neoplasms more often precede than follow B-cell lymphoma [2]. Nevertheless, in the majority of the reported cases [4], as well as in ours, the B-cell neoplasm preceded the T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of T and B non-Hodgkin's lymphomas (NHL) in the same patient is rare. Cutaneous T-cell lymphomas, such as MF and SS, have occasionally been described in association with myeloma [2], B-CLL [3], or other low-grade B-cell NHL [4]. Unusual cases associated with intermediate grade (centroblasticcentrocytic) lymphoma have also been reported [4].…”
Section: Introductionmentioning
confidence: 99%